Spring hydrographs recession and analysis of the Caposele spring (southern Italy) during dry periods - Fiorillo, Francesco (Italian journal of engineering geology and environment, 2013)
Hydrographs of the Caposele karst spring (Campania, Southern Italy) during the recession period have been analysed for last several years. A straight line was fitted to a semilogarithmic plot (log-discharge versus time), and the recession coefficient (the slope of the line generated from the equation) was calculated for each year considered. It has been found that the recession coefficient has positive a high correlation with discharge at the beginning of the recession period. For basal spring, this hydraulic behaviors has been explained by the model of FIORILLO (2011), who point out how the ratio between two different values of the recession coefficient obtained by the semilogarithmic plot can be approximated to the inverse ratio of the effective porosity computed along the surface of the water table (αII / αIII ≈ neffIII / neffII). Water level of a monitored well inside the karst catchment was also assessed and provided information on the water distribution into aquifers. Results describe the hydraulic behavior of karst aquifers during their emptying and provide information for better management of karst springs.